1998
DOI: 10.1159/000027305
|View full text |Cite
|
Sign up to set email alerts
|

The Protection of the Retina from Ischemic Injury by the Free Radical Scavenger EGb 761 and Zinc in the Cat Retina

Abstract: We investigated the effects of a free radical scavenger (EGb 761) and zinc in experimentally induced ischemic injury in the cat retina. Total retinal ischemia for 90 min was produced in the left eyes of 40 cats by raising intraocular pressure. In group 1, 10 cats were used as control. The free radical scavenger (EGb 761, 100 mg/kg) in group 2 (10 cats) and zinc chloride (250 μg/kg) in group 3 (10 cats) were administered intravenously at the end of ischemia. In group 4, both EGb 761 (100 mg/kg) and zinc chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 23 publications
(31 reference statements)
0
28
2
Order By: Relevance
“…Previous studies have demonstrated an elevated presence of free radicals in ischemic/reperfused rat retina, either directly by electron paramagnetic resonance [28] or indirectly by showing diminished damage after administering antioxidant drugs such as SOD, EGB 761 extracted from Ginkgo biloba, vitamin E, mannitol, CAT, and several other compounds [2,29,30]. Several studies have demonstrated the ischemic effect on retina as…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated an elevated presence of free radicals in ischemic/reperfused rat retina, either directly by electron paramagnetic resonance [28] or indirectly by showing diminished damage after administering antioxidant drugs such as SOD, EGB 761 extracted from Ginkgo biloba, vitamin E, mannitol, CAT, and several other compounds [2,29,30]. Several studies have demonstrated the ischemic effect on retina as…”
Section: Discussionmentioning
confidence: 99%
“…Daily dose of 120 mg of Ginkgo biloba was chosen based on information from prior clinical studies [23][24][25][26] suggesting a doseresponse relationship up to 240 mg [26]. Ginkgo biloba has been reported to protect various types of neurons in the central nervous system including cerebellum [27], cerebral cortex [28], basal ganglia [29], hippocampus [30] and retina [31] in various disorders like ischemia and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…A number of compounds targeting a variety of mechanisms including modulation of glutamate-induced excitotoxicity, [11][12][13][14] vascular regulation via inhibition of nitric oxide synthase 15,16 or the endothelin pathway, 17,18 oxidative stress, [19][20][21][22][23] and inhibition of glial activity 24,25 have been shown to be neuroprotective in animal models of glaucoma though few have been tested in formal clinical trials.…”
Section: Pharmacological Neuroprotectionmentioning
confidence: 99%